Social-Ecological Interactions Influencing Primate Harvest: Insights From Madagascar - Rivera, Christian J.; Mayo, Dominic; Hull, Vanessa (Frontiers in Conservation Science, 2021)
Globally, non-human primates face mounting threats due to unsustainable harvest by humans. There is a need to better understand the diverse drivers of primate harvest and the complex social-ecological interactions influencing harvest in shared human-primate systems. Here, we take an interdisciplinary, systems approach to assess how complex interactions among primate biological and ecological characteristics and human social factors affect primate harvest. We apply our approach through a review and synthesis of the literature on lemur harvest in Madagascar, a country with one of the highest primate species richness in the world coupled with high rates of threatened primate species and populations in decline. We identify social and ecological factors affecting primate harvest, including the characteristics of lemurs that may make them vulnerable to harvest by humans; factors describing human motivations for (or deterrents to) harvest; and political and governance factors related to power and accessibility. We then discuss social-ecological interactions that emerge from: 1) the prevalence of informal institutions (e.g. cultural taboos), 2) adoption of human predatory strategies, 3) synergies with habitat use and habitat loss, and 4) interactions among regional- and local-scale factors (multi-level interactions). Our results illustrate that social-ecological interactions influencing lemur harvest in Madagascar are complex and context-specific, while influenced by a combination of interactions between species-specific characteristics and human social factors. These context-specific interactions may be also influenced by local-level cultural practices, land use change, and effects from regional-level social complexities such as political upheaval and food insecurity. We conclude by discussing the importance of identifying and explicitly accounting for nuances in underlying social-ecological systems and putting forth ideas for future research on primate harvest in shared human-primate systems, including research on social-ecological feedbacks and the application of Routine Activities Theory.